Level of Knowledge Awareness and Use of Planning as Writing Strategy by EFL International Students in UUM English Intensive Course - Mohammed Ahmed Ado; Mohammad Othman Ahmad Alsheyab (Journal of English Language Teaching and Linguistics, 2019)
Malaysian English Language Curriculum makes it compulsory for every newly intake student to master and pass the English Writing Tasks (EWT) as among the basic skills in the language learning processes. However, most of the English Foreign Language (EFL) international students face difficulties with the EWT during the English Intensive Course (EIC) leading to consistent mass failures. The possible reasons of these failures could be due to the neglect of the writing strategies. Hence, the central focus of this paper is to identify and determine the EFL international students’ level of awareness and the use of planning as writing strategy before writing English essays. To this end, convenient purposive sampling strategy was used where 50 EFL (postgraduate and undergraduate) international students drawn from Universiti Utara Malaysian EIC program were selected and administered Writing Strategy Questionnaires (WSQ). The participants hailed from various countries who used and learned English as a foreign language, namely; Jordan, Iraq, Saudi Arabia, Libya, Palestine among others. The data were analyzed using SPSS. The findings revealed proportionate disparity between the EFL students that use planning strategy before starting writing English essays (usually true = 28%) with those that do not (usually not true = 28%). In terms of Revising Requirement for writing process before one start writing an essay in English, the findings revealed validity (40%) of participants’ responses at 82% cumulative. This is followed by “somewhat true” responses at 24% and 42% cumulative. These imply the EFL international students’ reasonable use of planning and having knowledge awareness of writing strategy